Three Adolescents With Primary Human Herpesvirus 7 Infection During a Measles Outbreak. Issue 8 (August 2020) - Kono, Toya; Hattori, Fumihiko; Kawamura, Yoshiki; Miura, Hiroki; Sudo, Yuta; Suzuki, Michio; Yoshikawa, Tetsushi
Abstract : During local small measles outbreak in Japan, 3 adolescents with febrile skin rash suspected as having measles were diagnosed with primary human herpesvirus (HHV)-7 infection. Primary HHV-7 infection can cause exanthem subitum in not only young children but also adolescents. HHV-7 should be considered as a possible causative agent for adolescent febrile skin rash during the measles outbreak.